HOW IS THE RATE OF INFLATION AND MONEY SUPPLY IN THAILAND? - Asengbaramae, Rowiyah (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Understanding the money supply process is crucial in that policymakers and related economic agents will know whether or not the central bank can conduct sound monetary policy. Most previous studies employ linear cointegration tests, which assume that the adjustment towards the long-run equilibrium is symmetric. However, when this long-run relationship is not linear, the results can be misleading. The type of research used is library research or literature study where researchers rely on various literatures to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. Between money supply and inflation is generally positive, especially over the long term. An increase in the money supply tends to lead to higher inflation if it outpaces economic growth.